Financial Independence, Accountability, Transparency, and Their Influence on Local Government Corruption in Sumatra Provinces - Rochmawati Daud; Rika Henda Safitri; Trie Sartika Pratiwi; Imelda Imelda; Maura Marcia Devana (Politeknik Ganesha Medan, 2026)
This study aims to analyze financial performance, accountability, and transparency in reducing corruption practices in Indonesia, particularly in provincial governments on the island of Sumatra. This study uses secondary data, namely Audit Reports (LHP), as well as corruption level data obtained from the Supreme Court website, with a sample of 10 city governments selected based on specific criteria (purposive sampling). A total of 50 observations were made from 2019 to 2023. Financial performance (independence ratio) had a significant effect on the level of corruption with a significance value of 0.0000 (<0.05) and a positive regression coefficient of 30.548, while accountability and transparency did not show a significant effect. This indicates that the higher the financial performance (independence ratio), the higher the level of corruption tends to be. Higher accountability does not necessarily reduce the level of corruption. Transparency of local government financial reports (LKPD) does not affect the level of government corruption